Dimensions of the Javanese culture and the role of Parents in instilling values in creative industry entrepreneurship - Hermawan, Agus; Arief, Mohammad; Patmi Rahayu, Wening (International Journal of Engineering and Technology, 2018)
This paper reveals how the sources of Javanese culture, which has been instilled by parents of children as the new generation of the successor to the family business, can act as values of sources of inspiration which shapes the behavior of entrepreneurship in the creative industry. Entrepreneurship in family businesses uses these Javanese values as the standards of the family's belief, which makes the principles as an identity that guides them in entrepreneurship and creates a way of life in the running entrepreneurialism. The method used in this research is a social constructionist, narrative and interpretive. The narrative-based research approach is done through data collection with depth interview, and non-participatory observation as well as analysis of the theme that create the methodological foundation. The ideas emerged and developed from in narrative face-to-face that became a proposition of research findings. Findings clearly indicate the relationship between Javanese cultures which is owned by parents has been the values that are believed by the second generation and this has motivated their behavior entrepreneurship, and impact the learning element of entrepreneurship, as well as orientation in entrepreneurship.Â The internalization of the values of Javanese culture Bapakisme (paternalism) and Rukun (harmony) have motivated the behavior of entrepreneurship when running a business relationship. Javanese cultural values implemented in the form of obedience to parents, keeping harmony, learning competitors, watching of God, sincere, assertive, fortune flows, trust, motivating, cultivation of religious values, and independent values. The research provides new insights into the culture of entrepreneurship at the local level and links the insights to the cultivation of cultural values in entrepreneurship, which is realized in everyday behavior. The construct built provides the possibility of new learning materials for the perpetrators of entrepreneurs in Indonesia, where 47% of the population of Indonesia is Javanese ethnicity.Â Â